The warden - Trollope, Anthony, frey50; Gilmour, Robin, 1943- (London ; New York : Penguin, 2004)
The tranquil atmosphere of the cathedral town of Barchester is shattered when a scandal breaks concerning the financial affairs of a Church-run almshouse for elderly men. In the ensuing furore, Septimus Harding, the almshouse's well-meaning warden, finds himself pitted against his daughter's suitor Dr John Bold, a zealous local reformer.
Reprinted with a revised further reading and a new chronology.
Originally published: 1855.
Keywords: Church of England; Hospitals -- England -- Employees; Older men -- Institutional care -- England; Clergy -- England -- Residence; England -- Social life and customs